Review of Sequential Access Method for Fingerprint Identification - G. Indrawan G. Indrawan; B. Sitohang B. Sitohang; S. Akbar S. Akbar (Universitas Ahmad Dahlan, 2012)
Real time fingerprint identification is usually equipped with specific computation machine architecture to optimize speed factor. Focusing on achieving better speed performance of fingerprint identification on common computation machine, a disquisition was conducted on sequential access method for fingerprint identification, with its underlying data structure designed to work with parallel processing. Hypothetically, parallel processing based on multi-cores processor technology, can give faster result without reducing accuracy. If multi core processor was detected, simultaneous processes would run on fingerprint matching-pairs to find its similarity score, respectively. Experiment confirms that speed performance of fingerprint identification using sequential access method with parallel processing outperforms the one without parallel processing. For both strategy, even though using parallel processing confirms faster result, experiment shows that searching time O(n) still linearly depends on number of fingerprints in database. Avoiding such searching time trend, hypothetically, need strategy of direct access method utilization.